Desenvolvimento de um front-end web para uma ferramenta de experimentação em cenários de mobile cloud computing - Pereira, Patrick da Silva (2022)
Smartphones have evolved a lot in recent times, but despite this evolution, they still have restrictions regarding computing power, battery life, and network connectivity. With this problem, the Mobile Cloud Computing paradigm emerged, which tries to supply the heaviest computing resources in the cloud. Its main idea is to transfer a task from the mobile environment to the cloud, process the task, and transmit the results to the mobile device, thus, this technique is called computational offloading. Over time, several offloading frameworks were created, but the scenarios did not match reality to experiment and evaluate heavy solutions. MCC Testbed emerged to meet the need for experiments and execution of custom scenarios, however, it needed a friendly interface for creating and managing experimentation scenarios. Therefore, the objective of this work is to create a front-end web application to help developers and researchers in the use of MCC Testbed. The application was developed using ReactJS and has features such as creating and running scenarios, accessing the device via Virtual Network Computing (VNC), adding, listing and running Android applications with Android Application Pack (APK) format for offloading tests, and consulting the executed logs. in tests in the Android application. Experiments were carried out in 3 use cases, in the first case, scenario creation, which calculates the creation time and use of Central Process Unit (CPU) and memory, in the second case, scenario execution, uses metrics of upload time, download time and run time on the server, and the third case, resource usage with VNC enabled, calculates the resource usage (CPU and memory) with VNC inhabited and not enabled. The results of the experiments demonstrate that it is possible to use the tool to replace the current interface via the Command Line Interface (CLI).